The Characterization of Lord Voldemort in Novel Harry Potter and The Half-Blood Prince by J.K Rowling Seen from Psychoanalysis - Nurul Fitri (Tell : Teaching of English Language and Literature Journal, 2018)
The science of psychoanalysis not only uses to reveal the behaviour of human, but it can be used also to analyze the literary works. This study concerns analyzing one of character in J.K Rowlingâ€™s novel Harry Potter and the Half-Blood Prince â€œLord Voldemortâ€ by using psychoalaysis approach. This study focuses on the relation characterization of Voldemort between his past event. The goal of this study is to find out the the character and characterization of Voldemort relate to Voldemortâ€™s life seen psychoanalysis.Utilizing the descriptive qualitative as method the results of this study are the character that is depicted in Voldemort is antagonist and static character, the development of Voldemortâ€™s characterization is found in four steps: Voldemortâ€™s childhood, adolescence, Tom Riddle after Hogwarts, and Tom Riddle transforms being Lord Voldemort. The id is a part of unconscious, likely influence the personality of Voldemort and every action that he takes. It causes he grow up to be a scary and horrible person and he also does a lot of vile actions to satisfy his desire and to avoid feeling anxiety and uncomfotable. Like, he feels anxious because he can die, so, to avoid his feeling he creates horcrux to beat the death.